2015
DOI: 10.1111/jonm.12298
|View full text |Cite
|
Sign up to set email alerts
|

Association between shift work and severity of depressive symptoms among female nurses: the Korea Nurses' Health Study

Abstract: Nursing professionals, managers and health policy makers need to understand the factors influencing depressive symptoms and to use appropriate interventions based on the severity and not just the onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 34 publications
3
55
2
1
Order By: Relevance
“…The included studies were performed in Korea (n = 5), United Kingdom (n = 1), The Netherlands (n = 1), Norway (n = 1), Sweden (n = 1), China (n = 1), and Brazil (n = 1). The age range of the study participants in 7 studies (78910131617) was from 15 to 90 years, and the mean age in 4 studies (10111314) was from 25 to 39.76 years. The year of enrollment for participants across studies ranged between 1995 and 2009.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were performed in Korea (n = 5), United Kingdom (n = 1), The Netherlands (n = 1), Norway (n = 1), Sweden (n = 1), China (n = 1), and Brazil (n = 1). The age range of the study participants in 7 studies (78910131617) was from 15 to 90 years, and the mean age in 4 studies (10111314) was from 25 to 39.76 years. The year of enrollment for participants across studies ranged between 1995 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Shift work is known to be associated with an increased risk of physical health problems of the workers such as metabolic syndrome, diabetes mellitus, cancer, and cardiovascular disease (456). Moreover, several observational studies have reported the association between night shift work and the risk of mental illnesses such as depression and anxiety (7891011121314151617). Among the mental illnesses, depression is considered a predictor of sickness absence and work disability among the working population (18).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of nurses on a shift work schedule, they showed that sleep disturbance is prevalent (70%) and that this is mediated by emotional disturbance and insomnia vulnerability, but not chronotype. Lee and coworkers 59 have also shown that nurses working shift work are at a 1.5 times increased likelihood of having greater symptoms of depression.…”
Section: Shift Work Disordermentioning
confidence: 96%
“…[39] Shiftworkers were also more likely to smoke, to regularly use non-prescription analgesic and gastroesophageal reflux medication, to report unhappiness with their finances and their jobs, fatigue and lack of enthusiasm. These indicators of reduced well-being were independent of confounding factors, and suggest that shiftwork had extensive negative effects on overall quality of life.…”
Section: Discussionmentioning
confidence: 99%